(untitled) (Research, Society and Development, 2020)
In this article, a literature review on meaningful learning and the CTS / CTSA approach (science, technology, society and environment) is carried out, where the concepts are organized in a pedagogical planning that will produce a teaching method. It aims to present a relationship between learning with a logical cognitive structure, where social awareness is carried out using the CTSA theme. The methodology consists of a literature review, a theoretical study. And finally, it presents the validation of the literature, proposing a significant learning in chemistry through the CTSA approach. The proposed form would be using the three pedagogical moments of Delizaoicov.